Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Motor Learning in Older Adults with Mild Cognitive Impairment: A Systematic Review - Kylie B. Tomlin; Ruth Akinlosotu; Emily F. Gorman; Emily Schmitt; Stephen Eaton; Kelly P. Westlake (Neuropsychology Review, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Clinical outcomes of operative vs interventional radiology management of severe blunt abdominal solid organ injury among hemodynamically stable pediatric trauma patients: A national analysis - Nikita Nunes Espat; Hazem Nasef; Philip Lee; Ruth Zagales; Brian Chin; Jacob Strouse; Donald Plumley; Stephen Hersperger; Adel Elkbuli (Next Research, 2025)

Effect of controlled human Plasmodium falciparum infection on B cell subsets in individuals with different levels of malaria immunity - Pilar Requena; Gloria Patricia Gómez-Pérez; Matthew B. B. McCall; Diana Barrios; Ruth Aguilar; Julia Fernández-Morata; Marta Vidal; Joseph J. Campo; Carla Sanchez; Maria Yazdabankhsh; B. Kim Lee Sim; Stephen L. Hoffman; et al. (Medical Microbiology and Immunology, 2025)
Continuous exposure to Plasmodium falciparum (Pf) has been associated with alterations in B cells. We investigated the effect of controlled human malaria infection (CHMI) on B cell phenotypes in individuals with different Pf immunity status: malaria-naïve, immunized with PfSPZ-CVac and semi-immune (lifelong-exposed) volunteers. Compared to naïve, semi-immune but not vaccinated individuals, had increased baseline frequencies of immature B cells (CD19 + CD10 + ), active naive (IgD + CD27 − CD21 − ) B cells, active atypical (IgD − CD27 − CD21 − ) memory B cells (MBCs), active classical (IgD − CD27 + CD21 − ) MBCs and CD1c + -B cells but lower frequencies of some IgG + -B cells. The frequencies of CD1c + active atypical MBCs correlated positively with anti-Pf antibodies and negatively with circulating eotaxin levels, while the opposite was observed for IgG + resting atypical MBCs. During early blood-stage infection (day 11 after CHMI), there was an expansion of resting classical (IgD − CD27 + CD21 + ) MBCs in all three groups. Vaccination, compared to placebo, altered the effect of CHMI on B cells, showing a positive association with resting classical MBCs (β = 0.190, 95% CI 0.011–0.368) and active naïve-PD1 + (β = 0.637, 95% CI 0.058 to 1.217) frequencies, and a negative one with CD1c + resting atypical MBCs (β = − 0.328, 95% CI − 0.621 to − 0.032). In addition, the sickle cell trait in semi-immune subjects altered the effect of CHMI on several B cells. In conclusion, lifelong but not vaccine exposure to malaria was associated with increased frequencies of multiple B cell subsets, with higher and lower percentages of CD1c and IgG expressing-cells, respectively. A single infection (CHMI) induces changes in B cell frequencies and is modulated by sickle cell trait and malaria-immunity status. Clinical Trials Registration NCT01624961, NCT02115516, and NCT02237586.

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Genome-wide association analysis identifies seven loci conferring resistance to multiple wheat foliar diseases, including brown and yellow rust resistance originating from Aegilops ventricosa - Keith A. Gardner; Bethany Love; Pauline Bansept-Basler; Tobias Barber; Simon Berry; Nick Bird; Finn Borum; Lesley Boyd; James K. M. Brown; Ruth Bryant; Paul Fenwick; David Feuerhelm; et al. (Theoretical and Applied Genetics, 2025)
We assembled a European bread wheat ( Triticum aestivum L.) association mapping panel ( n = 480) genotyped using a 90,000 feature single nucleotide polymorphism array, with the aim of identifying genetic loci controlling resistance to four fungal diseases: yellow (stripe) rust (YR), brown (leaf) rust (BR), Septoria tritici blotch (ST) and powdery mildew (PM). Simulations showed our panel to have good power to detect genetic loci, with > 50% probability of identifying loci controlling as little as 5% of the variance when heritability was 0.6 or more. Using disease infection data collected across 31 trials undertaken in five European countries, genome-wide association studies (GWAS) identified 34 replicated genetic loci (20 for YR, 12 for BR, two for PM, 0 for ST), with seven loci associated with resistance to two or more diseases. Construction and analysis of eight bi-parental populations enabled two selected genetic loci, yellow rust resistance locus YR_2A010 (chromosome 2A) and YR_6A610 (6A), to be independently cross-validated, along with the development of genetic markers to track resistance alleles at these loci. Notably, the chromosome 2A yellow and brown rust resistance locus corresponds to the 2N v S introgression from the wild wheat species, Aegilops ventricosa . We found evidence of strong selection for 2N v S over recent breeding history, being present in 48% of the most recent cultivars in our panel. Collectively, we define the genetic architectures controlling resistance to major fungal diseases of wheat under European field environments, and provide resources to exploit these for the development of new wheat cultivars with improved disease resistance.

Homing navigation is optimized to diurnal constraints in a tropical seabird, the red-footed booby - Joshua Coste; Stephen C. Votier; Ruth E. Dunn; Robin Freeman; Malcolm A. Nicoll; Peter Carr; Hannah Wood; Alice M. Trevail (Animal Behaviour, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Mechanistic safety assessment via multi-omic characterisation of systemic pathway perturbations following in vivo MAT2A inhibition - Valentina Fogal; Filippos Michopoulos; Andrew F. Jarnuczak; Ghaith M. Hamza; Stephanie Harlfinger; Paul Davey; Heather Hulme; Stephen J. Atkinson; Piotr Gabrowski; Tony Cheung; Michael Grondine; Clare Hoover; et al. (Archives of Toxicology, 2024)
The tumour suppressor p16/CDKN2A and the metabolic gene, methyl-thio-adenosine phosphorylase (MTAP), are frequently co-deleted in some of the most aggressive and currently untreatable cancers. Cells with MTAP deletion are vulnerable to inhibition of the metabolic enzyme, methionine-adenosyl transferase 2A (MAT2A), and the protein arginine methyl transferase (PRMT5). This synthetic lethality has paved the way for the rapid development of drugs targeting the MAT2A/PRMT5 axis. MAT2A and its liver- and pancreas-specific isoform, MAT1A, generate the universal methyl donor S-adenosylmethionine (SAM) from ATP and methionine. Given the pleiotropic role SAM plays in methylation of diverse substrates, characterising the extent of SAM depletion and downstream perturbations following MAT2A/MAT1A inhibition (MATi) is critical for safety assessment. We have assessed in vivo target engagement and the resultant systemic phenotype using multi-omic tools to characterise response to a MAT2A inhibitor (AZ’9567). We observed significant SAM depletion and extensive methionine accumulation in the plasma, liver, brain and heart of treated rats, providing the first assessment of both global SAM depletion and evidence of hepatic MAT1A target engagement. An integrative analysis of multi-omic data from liver tissue identified broad perturbations in pathways covering one-carbon metabolism, trans-sulfuration and lipid metabolism. We infer that these pathway-wide perturbations represent adaptive responses to SAM depletion and confer a risk of oxidative stress, hepatic steatosis and an associated disturbance in plasma and cellular lipid homeostasis. The alterations also explain the dramatic increase in plasma and tissue methionine, which could be used as a safety and PD biomarker going forward to the clinic.

Radical and incremental, a multi-leverage point approach to transformation in ocean governance - Tegan Evans; Stephen Fletcher; Pierre Failler; Ruth Fletcher; Jonathan Potts (Sustainability Science, 2024)
Urgent change is required in the governance of ocean spaces to contend with the increasing presence and impact of human activities, the solution to which is often labelled a ‘transformation.’ While diverse interpretations of this concept exist across academic disciplines, a grounded exploration of the subject with those involved in ocean governance has not been undertaken and is a critical gap in the practical implementation of the concept. Leverage points have been not only identified as a mechanism for change, but also face similar research challenges. Therefore, this research aimed to identify, through 24 expert and practitioner interviews, what exactly transformation means in the context of ocean governance, and how it can be achieved through a leverage points approach. While reactions to and perceptions of the concept were mixed, several definitions of transformation were identified, ultimately hinging on incremental and radical change to define character. A multi-intervention ‘puzzle’ style of leverage points is advocated for. Therefore, ocean governance transformation is proposed to be achieved through a model that recognises the utility and benefits of both radical and incremental change and employs a multi-leverage approach, using interventions at varying depths across the system.

From route to dive: multi-scale habitat selection in a foraging tropical seabird - Ruth E. Dunn; Robin Freeman; Malcolm A. Nicoll; Julia Ramsden; Alice M. Trevail; Hannah Wood; Stephen C. Votier (Marine Biology, 2024)
Comprehending how environmental variability shapes foraging behaviour across habitats is key to unlocking insights into consumer ecology. Seabirds breeding at high latitudes are exemplars of how marine consumers can adapt their behaviours to make use of predictable foraging opportunities, but prey tends to be less predictable in tropical oceanic ecosystems and may require alternative foraging behaviours. Here we used GPS and time-depth recorder loggers to investigate the foraging behaviour of central placed adult red-footed boobies ( Sula sula rubripes ), a tropical seabird that forages in oceanic waters via diving, or by capturing aerial prey such as flying fish in flight. Dive bout dynamics revealed that red-footed boobies appeared to exploit denser, but more sparsely distributed prey patches when diving further from the colony. Furthermore, although we found no evidence of environmentally driven habitat selection along their foraging routes, red-footed boobies preferentially dived in areas with higher sea surface temperatures and chlorophyll-a concentrations compared to conditions along their foraging tracks. This multi-scale variation implies that habitat selection differs between foraging routes compared to dive locations. Finally, red-footed booby dives were deepest during the middle of the day when light penetration was greatest. Ultimately, we highlight the importance of gaining insights into consumer foraging across different ecosystems, thereby broadening understanding of how animals might respond to changing environmental conditions.

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Trade-offs and Trait Integration in Tree Phenotypes: Consequences for the Sustainable Use of Genetic Resources - Jose Climent; Ricardo Alía; Katri Karkkainen; Catherine Bastien; Marta Benito-Garzon; Laurent Bouffier; Giovanbattista De Dato; Sylvain Delzon; Arnaud Dowkiw; Margarita Elvira-Recuenco; Delphine Grivet; Santiago C. González-Martínez; et al. (Current Forestry Reports, 2024)
Purpose of Review In this review, we synthesise current knowledge on trade-offs among traits in key fitness dimensions and identify major research gaps with the intention of laying the groundwork for a rapid advance in tree breeding for multiple objectives as a key contribution to the sustainability of planted forests in the future. Recent Findings Trade-offs among growth, reproduction, defence, stress tolerance and product quality predicted theoretically have been reported experimentally in many breeding programmes. Among these trade-offs, the genetic linkage between resistance against biotic threats and growth (or other relevant traits) is particularly critical for the current and future management of forest genetic resources. Maintaining tree growth and wood quality in the novel environments of the future requires the assessment of genetic correlations of target traits with phenology, closely linked to survival to temperature extremes. Improving our current knowledge on the genetic trade-offs of drought tolerance as a breeding objective in forest trees obligates a more precise definition of both the specific traits and the experimental conditions. Published evidence suggests that common target traits in breeding programmes may trade-off with reproductive success and fire-adaptation, and the simultaneous improvement of growth and wood quality traits still remains as a constraint in traditional tree breeding. Summary Changing environments combined with pests and diseases are challenging plantation forestry worldwide, which implies an urgent need to develop new improvement strategies to build the resilience of forestry for our future environments. It is essential to have a better understanding of how traits interact, especially those important for production, climate and biotic threat resilience, but much of the information is still missing. Since many key trade-offs are affected by the environment, we need new studies under novel environments to forecast levels of multi-trait integration in breeding populations.

Harmful algal blooms in Cayuga lake, NY: From microbiome analysis to eDNA monitoring - Nan Wang; Noah Mark; Nathaniel Launer; Adrianna Hirtler; Claire Weston; Lisa Cleckner; Chloe Faehndrich; Lydia LaGorga; Lingzi Xia; Daniel Pyrek; Stephen M. Penningroth; Ruth E. Richardson (Journal of Environmental Management, 2024)

Strong breeding colony fidelity in northern gannets following high pathogenicity avian influenza virus (HPAIV) outbreak - David Grémillet; Aurore Ponchon; Pascal Provost; Amandine Gamble; Mouna Abed-Zahar; Alice Bernard; Nicolas Courbin; Grégoire Delavaud; Armel Deniau; Jérôme Fort; Keith C. Hamer; Ruth Jeavons; et al. (Biological Conservation, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Antibody Fc-binding profiles and ACE2 affinity to SARS-CoV-2 RBD variants - Ebene R. Haycroft; Samantha K. Davis; Pradhipa Ramanathan; Ester Lopez; Ruth A. Purcell; Li Lynn Tan; Phillip Pymm; Bruce D. Wines; P. Mark Hogarth; Adam K. Wheatley; Jennifer A. Juno; Samuel J. Redmond; et al. (Medical Microbiology and Immunology, 2023)
Emerging SARS-CoV-2 variants, notably Omicron, continue to remain a formidable challenge to worldwide public health. The SARS-CoV-2 receptor-binding domain (RBD) is a hotspot for mutations, reflecting its critical role at the ACE2 interface during viral entry. Here, we comprehensively investigated the impact of RBD mutations, including 5 variants of concern (VOC) or interest—including Omicron (BA.2)—and 33 common point mutations, both on IgG recognition and ACE2-binding inhibition, as well as FcγRIIa- and FcγRIIIa-binding antibodies, in plasma from two-dose BNT162b2-vaccine recipients and mild-COVID-19 convalescent subjects obtained during the first wave using a custom-designed bead-based 39-plex array. IgG-recognition and FcγR-binding antibodies were decreased against the RBD of Beta and Omicron, as well as point mutation G446S, found in several Omicron sub-variants as compared to wild type. Notably, while there was a profound decrease in ACE2 inhibition against Omicron, FcγR-binding antibodies were less affected, suggesting that Fc functional antibody responses may be better retained against the RBD of Omicron in comparison to neutralization. Furthermore, while measurement of RBD–ACE2-binding affinity via biolayer interferometry showed that all VOC RBDs have enhanced affinity to human ACE2, we demonstrate that human ACE2 polymorphisms, E35K (rs1348114695) has reduced affinity to VOCs, while K26R (rs4646116) and S19P (rs73635825) have increased binding kinetics to the RBD of VOCs, potentially affecting virus–host interaction and, thereby, host susceptibility. Collectively, our findings provide in-depth coverage of the impact of RBD mutations on key facets of host–virus interactions.

Systemic innate myeloid responses to acute ischaemic and haemorrhagic stroke - Ruth Stephens; John R. Grainger; Craig J. Smith; Stuart M. Allan (Seminars in Immunopathology, 2023)
Acute ischaemic and haemorrhagic stroke account for significant disability and morbidity burdens worldwide. The myeloid arm of the peripheral innate immune system is critical in the immunological response to acute ischaemic and haemorrhagic stroke. Neutrophils, monocytes, and dendritic cells (DC) contribute to the evolution of pathogenic local and systemic inflammation, whilst maintaining a critical role in ongoing immunity protecting against secondary infections. This review aims to summarise the key alterations to myeloid immunity in acute ischaemic stroke, intracerebral haemorrhage (ICH), and subarachnoid haemorrhage (SAH). By integrating clinical and preclinical research, we discover how myeloid immunity is affected across multiple organ systems including the brain, blood, bone marrow, spleen, and lung, and evaluate how these perturbations associate with real-world outcomes including infection. These findings are placed in the context of the rapidly developing field of human immunology, which offers a wealth of opportunity for further research.

Mink on the brink: comparing survey methods for detecting a critically endangered carnivore, the European mink Mustela lutreola - Elizabeth Croose; Ruth Hanniffy; Andrew Harrington; Madis Põdra; Asun Gómez; Polly L. Bolton; Jenna V. Lavin; Samuel S. Browett; Javier Pinedo; David Lacanal; Iñaki Galdos; Jon Ugarte; et al. (European Journal of Wildlife Research, 2023)
Monitoring rare and elusive species is critical in guiding appropriate conservation management measures. Mammalian carnivores are challenging to monitor directly, due to their generally nocturnal and solitary lifestyle, and relatively large home ranges. The European mink Mustela lutreola is a critically endangered, small, semi-aquatic carnivore and is one of the most threatened mammal species in Europe. In northern Spain, the European mink population is monitored regionally using different methods and approaches, making assessment of national population status difficult. There is an urgent need to 1) assess the efficacy of survey methods and 2) identify a standard monitoring methodology that can be deployed rapidly and inexpensively over large areas of the mink’s range. We deployed four methods—camera trapping, hair tubes, live trapping, and environmental DNA (eDNA) from water samples—to compare the probability of detecting European mink when present at 25 sampling sites within five 10 × 10 km 2 , and the economic cost and time required for each method. All four methods successfully detected European mink but the probability of detection varied by method. Camera trapping and hair tubes had the highest probability of detection; however, eDNA and live trapping detected mink in one 10 × 10 km 2 where the latter two methods did not. For future European mink monitoring programs, we recommend a combination of at least two methods and suggest that camera traps or hair tubes are combined with live trapping or eDNA (depending on the scale and aims of the study), to gather critical information on distribution, occupancy and conservation status.

A globally relevant change taxonomy and evidence‐based change framework for land monitoring - Richard M. Lucas; Sophia German; Graciela Metternicht; Rebecca K. Schmidt; Christopher J. Owers; Suzanne M. Prober; Anna E. Richards; Sally Tetreault‐Campbell; Kristen J. Williams; Norman Mueller; Belle Tissott; Sean M. T. Chua; et al. (Global Change Biology, 2022)
A globally relevant and standardized taxonomy and framework for consistently describing land cover change based on evidence is presented, which makes use of structured land cover taxonomies and is underpinned by the Driver‐Pressure‐State‐Impact‐Response (DPSIR) framework. The Global Change Taxonomy currently lists 246 classes based on the notation ‘impact (pressure)’, with this encompassing the consequence of observed change and associated reason(s), and uses scale‐independent terms that factor in time. Evidence for different impacts is gathered through temporal comparison (e.g., days, decades apart) of land cover classes constructed and described from Environmental Descriptors (EDs; state indicators) with pre‐defined measurement units (e.g., m, %) or categories (e.g., species type). Evidence for pressures, whether abiotic, biotic or human‐influenced, is similarly accumulated, but EDs often differ from those used to determine impacts. Each impact and pressure term is defined separately, allowing flexible combination into ‘impact (pressure)’ categories, and all are listed in an openly accessible glossary to ensure consistent use and common understanding. The taxonomy and framework are globally relevant and can reference EDs quantified on the ground, retrieved/classified remotely (from ground‐based, airborne or spaceborne sensors) or predicted through modelling. By providing capacity to more consistently describe change processes—including land degradation, desertification and ecosystem restoration—the overall framework addresses a wide and diverse range of local to international needs including those relevant to policy, socioeconomics and land management. Actions in response to impacts and pressures and monitoring towards targets are also supported to assist future planning, including impact mitigation actions.

Genetic patterns in Montipora capitata across an environmental mosaic in Kāne'ohe Bay, O'ahu, Hawai'i - Carlo Caruso; Mariana Rocha de Souza; Lupita Ruiz‐Jones; Dennis Conetta; Joshua Hancock; Callum Hobbs; Caroline Hobbs; Valerie Kahkejian; Rebecca Kitchen; Christian Marin; Stephen Monismith; Joshua Madin; et al. (Molecular Ecology, 2022)
Spatial genetic structure (SGS) is important to a population's ability to adapt to environmental change. For species that reproduce both sexually and asexually, the relative contribution of each reproductive mode has important ecological and evolutionary implications because asexual reproduction can have a strong effect on SGS. Reef‐building corals reproduce sexually, but many species also propagate asexually under certain conditions. To understand SGS and the relative importance of reproductive mode across environmental gradients, we evaluated genetic relatedness in almost 600 colonies of Montipora capitata across 30 environmentally characterized sites in Kāneʻohe Bay, Oʻahu, Hawaii, using low‐depth restriction digest‐associated sequencing. Clonal colonies were relatively rare overall but influenced SGS. Clones were located significantly closer to one another spatially than average colonies and were more frequent on sites where wave energy was relatively high, suggesting a strong role of mechanical breakage in their formation. Excluding clones, we found no evidence of isolation by distance within sites or across the bay. Several environmental characteristics were significant predictors of the underlying genetic variation (including degree heating weeks, time spent above 30°C, depth, sedimentation rate and wave height); however, they only explained 5% of this genetic variation. Our results show that asexual fragmentation contributes to the ecology of branching corals at local scales and that genetic diversity is maintained despite strong environmental gradients in a highly impacted ecosystem, suggesting potential for broad adaptation or acclimatization in this population.

The protist community traces seasonality and mesoscale hydrographic features in the oligotrophic Sargasso Sea - Leocadio Blanco-Bercial; Rachel Parsons; Luis M. Bolaños; Rod Johnson; Stephen J. Giovannoni; Ruth Curry (Frontiers in Marine Science, 2022)
Protists represent the majority of the eukaryotic diversity in the oceans. They have different functions in the marine food web, playing essential roles in the biogeochemical cycles. While the available data is rich in horizontal and temporal coverage, little is known on their vertical structuring, particularly below the photic zone. The present study applies V4 18S rDNA metabarcoding to samples collected over three years in conjunction with the BATS time-series to assess marine protist communities in the epipelagic and mesopelagic zones (0-1000 m). The protist community showed a dynamic seasonality in the epipelagic, responding to hydrographic yearly cycles. Mixotrophic lineages dominated throughout the year. However, autotrophs bloomed during the rapid transition between the winter mixing and the stratified summer, and heterotrophs had their peak at the end of summer, when the base of the thermocline reaches its deepest depth. Below the photic zone, the community, dominated by Rhizaria, is depth-stratified and relatively constant throughout the year, although they followed local hydrographic and biological features such as the oxygen minimum zone. The results suggest a dynamic partitioning of the water column, where the niche vertical position for each community changes throughout the year in the epipelagic, likely depending on nutrient availability, the mixed layer depth, and other hydrographic features. At depth, the protist community closely tracked mesoscale events (eddies), where the communities followed the hydrographic uplift, raising the deeper communities for hundreds of meters, and compressing the communities above.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Biogeochemical consequences of a changing Arctic shelf seafloor ecosystem - Christian März; Felipe S. Freitas; Johan C. Faust; Jasmin A. Godbold; Sian F. Henley; Allyson C. Tessin; Geoffrey D. Abbott; Ruth Airs; Sandra Arndt; David K. A. Barnes; Laura J. Grange; Neil D. Gray; et al. (Ambio, 2022)
Unprecedented and dramatic transformations are occurring in the Arctic in response to climate change, but academic, public, and political discourse has disproportionately focussed on the most visible and direct aspects of change, including sea ice melt, permafrost thaw, the fate of charismatic megafauna, and the expansion of fisheries. Such narratives disregard the importance of less visible and indirect processes and, in particular, miss the substantive contribution of the shelf seafloor in regulating nutrients and sequestering carbon. Here, we summarise the biogeochemical functioning of the Arctic shelf seafloor before considering how climate change and regional adjustments to human activities may alter its biogeochemical and ecological dynamics, including ecosystem function, carbon burial, or nutrient recycling. We highlight the importance of the Arctic benthic system in mitigating climatic and anthropogenic change and, with a focus on the Barents Sea, offer some observations and our perspectives on future management and policy.

Assessing the detectability of the Irish stoat Mustela erminea hibernica using two camera trap-based survey methods - Elizabeth Croose; Ruth Hanniffy; Brian Hughes; Kate McAney; Jenny MacPherson; Stephen P. Carter (Mammal Research, 2022)

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Carbohydrate mouth rinsing does not affect 6-min walk test performance and blood glucose responses in older adults - Elizabeth S. Evans; Terrence Brophy; Matthew R. Braswell; Joshua Boyle; G. Keith Harris; Ruth H. Watkins; Stephen P. Bailey (European Journal of Applied Physiology, 2021)

Negative Food Effect of Danirixin: Use of PBPK Modelling to Explore the Effect of Formulation and Meal Type on Clinical PK - Richard S. Lloyd; Martin I. Hingle; Jackie C. Bloomer; Stephen J. Charles; James M. Butler; Alan Paul; Xiaofeng Zhu; Bruce Miller; Donald D’Amico; Alison Donald; Ruth Tal-Singer; Claire Ambery (Pharmaceutical Research, 2020)

Toward indicators of the performance of US infrastructures under climate change risks - Thomas J. Wilbanks; Rae Zimmerman; Susan Julius; Paul Kirshen; Joel B. Smith; Richard Moss; William Solecki; Matthias Ruth; Stephen Conrad; Steven J. Fernandez; Michael S. Matthews; Michael J. Savonis; et al. (Climatic Change, 2020)

Relationship between faecal metronidazole and lactoferrin concentrations to clinical response of patients with Clostridioides difficile - Maria Saunders; Jinny Jeffery; Zoe Vincent; Ruth M. Ayling; Stephen Lewis (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Immunosignature Analysis of Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS) - Oliver P. Günther; Jennifer L. Gardy; Phillip Stafford; Øystein Fluge; Olav Mella; Patrick Tang; Ruth R. Miller; Shoshana M. Parker; Stephen A. Johnston; David M. Patrick (Molecular Neurobiology, 2019)

Diabetes and differences in detection of incident invasive breast cancer - Gregory S. Calip; Onchee Yu; Denise M. Boudreau; Huibo Shao; Ruth Oratz; Stephen B. Richardson; Heather T. Gold (Cancer Causes & Control, 2019)

Genome-wide association study of primary open-angle glaucoma in continental and admixed African populations - Pieter W. M. Bonnemaijer; Adriana I. Iglesias; Girish N. Nadkarni; Anna J. Sanyiwa; Hassan G. Hassan; Colin Cook; Mark Simcoe; Kent D. Taylor; Claudia Schurmann; Gillian M. Belbin; Eimear E. Kenny; Erwin P. Bottinger; et al. (Human Genetics, 2018)

Diet has independent effects on the pace and shape of aging in Drosophila melanogaster - C. Ruth Archer; Ugofilippo Basellini; John Hunt; Stephen J. Simpson; Kwang Pum Lee; Annette Baudisch (Biogerontology, 2018)

Limitation of dimethylsulfoniopropionate synthesis at high irradiance in natural phytoplankton communities of the Tropical Atlantic - Stephen D. Archer; Jacqueline Stefels; Ruth L. Airs; Tracy Lawson; Timothy J. Smyth; Andrew P. Rees; Richard J. Geider (Limnology and Oceanography, 2018)
Predictions of the ocean‐atmosphere flux of dimethyl sulfide will be improved by understanding what controls seasonal and regional variations in dimethylsulfoniopropionate (DMSP) production. To investigate the influence of high levels of irradiance including ultraviolet radiation (UVR), on DMSP synthesis rates ( μ DMSP) and inorganic carbon fixation ( μ POC) by natural phytoplankton communities, nine experiments were carried out at different locations in the low nutrient, high light environment of the northeastern Tropical Atlantic. Rates of μ DMSP and μ POC were determined by measuring the incorporation of inorganic 13 C into DMSP and particulate organic carbon. Based on measurements over discrete time intervals during the day, a unique μ DMSP vs. irradiance (P vs. E) relationship was established. Comparison is made with the P vs. E relationship for μ POC, indicating that light saturation of μ DMSP occurs at similar irradiance to μ POC and is closely coupled to carbon fixation on a diel basis. Photoinhibition during the middle of the day was exacerbated by exposure to UVR, causing an additional 55–60% inhibition of both μ DMSP and μ POC at the highest light levels. In addition, decreased production of DMSP in response to UVR‐induced photoxidative stress, contrasted with the increased net synthesis of photoprotective xanthophyll pigments. Together these results indicate that DMSP production by phytoplankton in the tropical ocean is not regulated in the short term by the necessity to control increasing photooxidative stress as irradiance increases during the day. The study provides new insight into the regulation of resource allocation into this biogeochemically important, multi‐functional compatible solute.

Research priorities for managing the impacts and dependencies of business upon food, energy, water and the environment - Jonathan M. H. Green; Gemma R. Cranston; William J. Sutherland; Hannah R. Tranter; Sarah J. Bell; Tim G. Benton; Eva Blixt; Colm Bowe; Sarah Broadley; Andrew Brown; Chris Brown; Neil Burns; et al. (Sustainability Science, 2017)

Diet and environment 1.2 million years ago revealed through analysis of dental calculus from Europe’s oldest hominin at Sima del Elefante, Spain - Karen Hardy; Anita Radini; Stephen Buckley; Ruth Blasco; Les Copeland; Francesc Burjachs; Josep Girbal; Riker Yll; Eudald Carbonell; Jose María Bermúdez de Castro (The Science of Nature, 2017)

Marine Microalgae: Climate, Energy, and Food Security from the Sea - Charles Greene; Mark Huntley; Ian Archibald; Léda Gerber; Deborah Sills; Joe Granados; Jefferson Tester; Colin Beal; Michael Walsh; Robert Bidigare; Susan Brown; William Cochlan; et al. (Oceanography, 2016)

The effects of height and BMI on prostate cancer incidence and mortality: a Mendelian randomization study in 20,848 cases and 20,214 controls from the PRACTICAL consortium - Neil M. Davies; Tom R. Gaunt; Sarah J. Lewis; Jeff Holly; Jenny L. Donovan; Freddie C. Hamdy; John P. Kemp; Rosalind Eeles; Doug Easton; Zsofia Kote-Jarai; Ali Amin Al Olama; Sara Benlloch; et al. (Cancer Causes & Control, 2015)

The Effects of Chronological Age and Size on Toxicity of Zinc to Juvenile Brown Trout - Daniel J. Diedrich; Ruth M. Sofield; James F. Ranville; Dale J. Hoff; V. Dan Wall; Stephen F. Brinkman (Archives of Environmental Contamination and Toxicology, 2015)

Identification of proteins capable of metal reduction from the proteome of the Gram‐positive bacterium D esulfotomaculum reducens MI ‐1 using an NADH ‐based activity assay - Anne Elyse Otwell; Robert W. Sherwood; Sheng Zhang; Ornella D. Nelson; Zhi Li; Hening Lin; Stephen J. Callister; Ruth E. Richardson (Environmental Microbiology, 2015)
Summary Understanding of microbial metal reduction is based almost solely on studies of G ram‐negative organisms. In this study, we focus on D esulfotomaculum reducens MI ‐1, a G ram‐positive metal reducer whose genome lacks genes with similarity to any characterized metal reductase. Using non‐denaturing separations and mass spectrometry identification, in combination with a colorimetric screen for chelated F e( III )‐ NTA reduction with NADH as electron donor, we have identified proteins from the D . reducens proteome not previously characterized as iron reductases. Their function was confirmed by heterologous expression in E scherichia coli . Furthermore, we show that these proteins have the capability to reduce soluble C r( VI ) and U ( VI ) with NADH as electron donor. The proteins identified are NADH : flavin oxidoreductase ( D red_2421) and a protein complex composed of oxidoreductase flavin adenine dinucleotide/ NAD ( P )‐binding subunit ( D red_1685) and dihydroorotate dehydrogenase 1B ( D red_1686). D red_2421 was identified in the soluble proteome and is predicted to be a cytoplasmic protein. D red_1685 and D red_1686 were identified in both the soluble as well as the insoluble protein fraction, suggesting a type of membrane association, although PSORTb predicts both proteins are cytoplasmic. This study is the first functional proteomic analysis of D . reducens and one of the first analyses of metal and radionuclide reduction in an environmentally relevant G ram‐positive bacterium.

BAAD: a Biomass And Allometry Database for woody plants - Daniel S. Falster; Remko A. Duursma; Masae I. Ishihara; Diego R. Barneche; Richard G. FitzJohn; Angelica Vårhammar; Masahiro Aiba; Makoto Ando; Niels Anten; Michael J. Aspinwall; Jennifer L. Baltzer; Christopher Baraloto; et al. (Ecology, 2015)
Understanding how plants are constructed—i.e., how key size dimensions and the amount of mass invested in different tissues varies among individuals—is essential for modeling plant growth, carbon stocks, and energy fluxes in the terrestrial biosphere. Allocation patterns can differ through ontogeny, but also among coexisting species and among species adapted to different environments. While a variety of models dealing with biomass allocation exist, we lack a synthetic understanding of the underlying processes. This is partly due to the lack of suitable data sets for validating and parameterizing models. To that end, we present the Biomass And Allometry Database (BAAD) for woody plants. The BAAD contains 259 634 measurements collected in 176 different studies, from 21 084 individuals across 678 species. Most of these data come from existing publications. However, raw data were rarely made public at the time of publication. Thus, the BAAD contains data from different studies, transformed into standard units and variable names. The transformations were achieved using a common workflow for all raw data files. Other features that distinguish the BAAD are: (i) measurements were for individual plants rather than stand averages; (ii) individuals spanning a range of sizes were measured; (iii) plants from 0.01–100 m in height were included; and (iv) biomass was estimated directly, i.e., not indirectly via allometric equations (except in very large trees where biomass was estimated from detailed sub‐sampling). We included both wild and artificially grown plants. The data set contains the following size metrics: total leaf area; area of stem cross‐section including sapwood, heartwood, and bark; height of plant and crown base, crown area, and surface area; and the dry mass of leaf, stem, branches, sapwood, heartwood, bark, coarse roots, and fine root tissues. We also report other properties of individuals (age, leaf size, leaf mass per area, wood density, nitrogen content of leaves and wood), as well as information about the growing environment (location, light, experimental treatment, vegetation type) where available. It is our hope that making these data available will improve our ability to understand plant growth, ecosystem dynamics, and carbon cycling in the world's vegetation.

Potential Applicability of Persuasive Communication to Light-Glow Reduction Efforts: A Case Study of Marine Turtle Conservation - Ruth L. Kamrowski; Stephen G. Sutton; Renae C. Tobin; Mark Hamann (Environmental Management, 2014)

Synergies and tradeoffs between cash crop production and food security: a case study in rural Ghana - Tal Lee Anderman; Roseline Remans; Stephen A. Wood; Kyle DeRosa; Ruth S. DeFries (Food Security, 2014)

Ion transporters in brain endothelial cells that contribute to formation of brain interstitial fluid - Ruth Mokgokong; Shanshan Wang; Caroline J. Taylor; Margery A. Barrand; Stephen B. Hladky (Pflügers Archiv - European Journal of Physiology, 2014)

Pyrogeography, historical ecology, and the human dimensions of fire regimes - Christopher I. Roos; David M. J. S. Bowman; Jennifer K. Balch; Paulo Artaxo; William J. Bond; Mark Cochrane; Carla M. D'Antonio; Ruth DeFries; Michelle Mack; Fay H. Johnston; Meg A. Krawchuk; Christian A. Kull; et al. (Journal of Biogeography, 2014)
In our 2011 synthesis (Bowman et al ., Journal of Biogeography , 2011, 38 , 2223–2236), we argued for a holistic approach to human issues in fire science that we term ‘pyrogeography’. Coughlan & Petty ( Journal of Biogeography , 2013, 40 , 1010–1012) critiqued our paper on the grounds that our ‘pyric phase’ model was built on outdated views of cultural development, claiming we developed it to be the unifying explanatory framework for all human–fire sciences. Rather, they suggest that ‘historical ecology’ could provide such a framework. We used the ‘pyric transition’ for multiple purposes but did not offer it as an exclusive explanatory framework for pyrogeography. Although ‘historical ecology’ is one of many useful approaches to studying human–fire relationships, scholars should also look to political and evolutionary ecology, ecosystems and complexity theories, as well as empirical generalizations to build an interdisciplinary fire science that incorporates human, ecological and biophysical dimensions of fire regimes.

Erratum to: α-Tocopheryl succinate causes mitochondrial permeabilization by preferential formation of Bak channels - Lubomir Prochazka; Lan-Feng Dong; Karel Valis; Ruth Freeman; Stephen J. Ralph; Jaroslav Turanek; Jiri Neuzil (Apoptosis, 2013)

Facial asymmetry is negatively related to condition in female macaque monkeys - Anthony C. Little; Annika Paukner; Ruth A. Woodward; Stephen J. Suomi (Behavioral Ecology and Sociobiology, 2012)

Explaining the variation in the soil microbial community: do vegetation composition and soil chemistry explain the same or different parts of the microbial variation? - Ruth Joy Mitchell; Alison J. Hester; Colin D. Campbell; Stephen J. Chapman; Clare M. Cameron; Richard L. Hewison; Jackie M. Potts (Plant and Soil, 2012)

Population processes in European Blackbirds Turdus merula: a state–space approach - Robert A. Robinson; Stephen R. Baillie; Ruth King (Journal of Ornithology, 2012)

Physiological consequences of military high-speed boat transits - Stephen D. Myers; Trevor D. Dobbins; Stuart King; Benjamin Hall; Ruth M. Ayling; Sharon R. Holmes; Tom Gunston; Rosemary Dyson (European Journal of Applied Physiology, 2011)

Erratum to: Meat, poultry and fish and risk of colorectal cancer: pooled analysis of data from the UK dietary cohort consortium - Elizabeth A. Spencer; Timothy J. Key; Paul N. Appleby; Christina C. Dahm; Ruth H. Keogh; Ian S. Fentiman; Tasnime Akbaraly; Eric J. Brunner; Victoria Burley; Janet E. Cade; Darren C. Greenwood; Alison M. Stephen; et al. (Cancer Causes & Control, 2011)

Lack of germline PALB2 mutations in melanoma-prone families with CDKN2A mutations and pancreatic cancer - Xiaohong R. Yang; Lea Jessop; Timothy Myers; Laufey Amundadottir; Ruth M. Pfeiffer; William Wheeler; Kristen M. Pike; Jeff Yuenger; Laurie Burdett; Meredith Yeager; Stephen J. Chanock; Margaret A. Tucker; et al. (Familial Cancer, 2011)

Cysteine residue 911 in C-terminal tail of human BKCaα channel subunit is crucial for its activation by carbon monoxide - Vsevolod Telezhkin; Stephen P. Brazier; Ruth Mears; Carsten T. Müller; Daniela Riccardi; Paul J. Kemp (Pflügers Archiv - European Journal of Physiology, 2011)

Germline PKHD1 mutations are protective against colorectal cancer - Christopher J. Ward; Yanhong Wu; Ruth A. Johnson; John R. Woollard; Eric J. Bergstralh; Mine S. Cicek; Jason Bakeberg; Sandro Rossetti; Christina M. Heyer; Gloria M. Petersen; Noralene M. Lindor; Stephen N. Thibodeau; et al. (Human Genetics, 2011)

Associations of 9p21 variants with cutaneous malignant melanoma, nevi, and pigmentation phenotypes in melanoma-prone families with and without CDKN2A mutations - Xiaohong Rose Yang; Xueying Liang; Ruth M. Pfeiffer; William Wheeler; Dennis Maeder; Laurie Burdette; Meredith Yeager; Stephen Chanock; Margaret A. Tucker; Alisa M. Goldstein (Familial Cancer, 2010)

Meat, poultry and fish and risk of colorectal cancer: pooled analysis of data from the UK dietary cohort consortium - Elizabeth A. Spencer; Timothy J. Key; Paul N. Appleby; Christina C. Dahm; Ruth H. Keogh; Ian S. Fentiman; Tasnime Akbaraly; Eric J. Brunner; Victoria Burley; Janet E. Cade; Darren C. Greenwood; Alison M. Stephen; et al. (Cancer Causes & Control, 2010)

Is vegetation composition or soil chemistry the best predictor of the soil microbial community? - Ruth J. Mitchell; Alison J. Hester; Colin D. Campbell; Stephen J. Chapman; Clare M. Cameron; Richard L. Hewison; Jackie M. Potts (Plant and Soil, 2010)

α-Tocopheryl succinate causes mitochondrial permeabilization by preferential formation of Bak channels - Lubomir Prochazka; Lan-Feng Dong; Karel Valis; Ruth Freeman; Stephen J. Ralph; Jaroslav Turanek; Jiri Neuzil (Apoptosis, 2010)

Dimethyl sulfoniopropionate and dimethyl sulfide production in response to photoinhibition in Emiliania huxleyi - Stephen D. Archer; Maria Ragni; Richard Webster; Ruth L. Airs; Richard J. Geider (Limnology and Oceanography, 2010)
The response in intracellular dimethyl sulfoniopropionate (DMSP) and dissolved DMSP and dimethyl sulfide (DMS) concentrations when Emiliania huxleyi was exposed to acute (1‐h) increases in photon flux densities of photosynthetically active radiation (PAR) and ultraviolet (UV) radiation was examined in cells acclimated to low light (LL, 30 µmol photons m −2 s −1 ) and high light (HL, 300 vmol photons m −2 s −1 ). LL‐acclimated cells displayed greater photoinhibition, assessed as a decrease in maximum photochemical efficiency ( F v : F m ). Photoinhibition was increased by exposure to UV wavelengths. LL‐acclimated cells also exhibited more light dissipation through the xanthophyll cycle, evident as changes in de‐epoxidation state. Greater photoinhibition in LL‐acclimated cells corresponded with increased accumulation of DMSP of 21% ± 4% relative to initial concentrations, contrasting with a slight decrease of 5% ± 6% in HL‐acclimated cells. Exposure to UV appeared to decrease the rates of intracellular accumulation of DMSP. Conversely, PAR + UV exposure stimulated the net production of dissolved DMSP and DMS in both HL‐acclimated and LL‐acclimated cultures, compared with high PAR alone. The results indicate a direct link between acute photo‐oxidative stress and DMSP synthesis by E. huxleyi . The physiological basis for increased release of DMSP and DMS from cells due to high PAR + UV exposure is unclear. However, the timescales of changes in intracellular DMSP, dissolved DMSP, and DMS are consistent with variations in light intensity experienced by phytoplankton in a turbulent mixed layer and are similar to rates of change in photosynthetic parameters associated with photoacclimation.

A review of allograft ophthalmic tissue in eye surgery - Andrew Baddon; Mark Jones; John Armitage; Ruth Warwick; Stephen Kaye (Cell and Tissue Banking, 2010)

A UK scheme for reporting serious adverse events and reactions associated with ocular tissue transplantation - Stephen Kaye; Andrew Baddon; Mark Jones; W. John Armitage; Deirdre Fehily; Ruth M. Warwick (Cell and Tissue Banking, 2010)

Implications of future climate and atmospheric CO 2 content for regional biogeochemistry, biogeography and ecosystem services across East Africa - RUTH M. DOHERTY; STEPHEN SITCH; BENJAMIN SMITH; SIMON L. LEWIS; PHILIP K. THORNTON (Global Change Biology, 2010)
We model future changes in land biogeochemistry and biogeography across East Africa. East Africa is one of few tropical regions where general circulation model (GCM) future climate projections exhibit a robust response of strong future warming and general annual‐mean rainfall increases. Eighteen future climate projections from nine GCMs participating in the Intergovernmental Panel on Climate Change (IPCC) Fourth Assessment were used as input to the LPJ dynamic global vegetation model (DGVM), which predicted vegetation patterns and carbon storage in agreement with satellite observations and forest inventory data under the present‐day climate. All simulations showed future increases in tropical woody vegetation over the region at the expense of grasslands. Regional increases in net primary productivity (NPP) (18–36%) and total carbon storage (3–13%) by 2080–2099 compared with the present‐day were common to all simulations. Despite decreases in soil carbon after 2050, seven out of nine simulations continued to show an annual net land carbon sink in the final decades of the 21st century because vegetation biomass continued to increase. The seasonal cycles of rainfall and soil moisture show future increases in wet season rainfall across the GCMs with generally little change in dry season rainfall. Based on the simulated present‐day climate and its future trends, the GCMs can be grouped into four broad categories. Overall, our model results suggest that East Africa, a populous and economically poor region, is likely to experience some ecosystem service benefits through increased precipitation, river runoff and fresh water availability. Resulting enhancements in NPP may lead to improved crop yields in some areas. Our results stand in partial contradiction to other studies that suggest possible negative consequences for agriculture, biodiversity and other ecosystem services caused by temperature increases.

The transcription factor GATA-2 does not associate with angiographic coronary artery disease in the Ottawa Heart Genomics and Cleveland Clinic GeneBank Studies - Sonny Dandona; Li Chen; Meng Fan; Md Afaque Alam; Olivia Assogba; Melanie Belanger; Kathryn Williams; George A. Wells; W. H. Wilson Tang; Stephen G. Ellis; Stanley L. Hazen; Ruth McPherson; et al. (Human Genetics, 2010)

Scale-specific correlations between habitat heterogeneity and soil fauna diversity along a landscape structure gradient - Adam J. Vanbergen; Allan D. Watt; Ruth Mitchell; Anne-Marie Truscott; Stephen C. F. Palmer; Eva Ivits; Paul Eggleton; T. Hefin Jones; José Paulo Sousa (Oecologia, 2007)

The reliability of immunohistochemistry as a prescreening method for the diagnosis of hereditary nonpolyposis colorectal cancer (HNPCC) – Results of an international collaborative study - Wolfram Müller; Lawrence J. Burgart; Ruth Krause-Paulus; Stephen N. Thibodeau; M. Almeida; T. Brocker Edmonston; C. R. Boland; C. Sutter; J. R. Jass; A. Lindblom; J. Lubinski; K. MacDermot; et al. (Familial Cancer, 2001)

Flies that are parasitoids of a marine snail: the larviposition behaviour and life cycles of Sarcophaga megafilosia and Sarcophaga meiofilosia - Stephen C. McKillup; Ruth V. McKillup; Thomas Pape (Hydrobiologia, 2000)

Modeling biotic and abiotic influences on population size in small mammals - Ruth H. Lewellen; Stephen H. Vessey (Oecologia, 1998)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

The relationship between dietary fat intake and risk of colorectal cancer: evidence from the combined analysis of 13 case-control studies - Geoffrey R. Howe; Kristan J. Aronson; Enrique Benito; Roberto Castelleto; Jacqueline Cornée; Stephen Duffy; Richard P. Gallagher; José M. Iscovich; Jiao Deng-ao; Rudolf Kaaks; Gabriel A. Kune; Susan Kune; et al. (Cancer Causes & Control, 1997)

A knowledge-based expert system for planning and design of agroforestry systems - Merrill E. Warkentin; P. K. R. Nair; Stephen R. Ruth; Kristopher Sprague (Agroforestry Systems, 1990)